Cytogenetic Analysis and Molecular Marker Development for a New Wheat–Thinopyrum ponticum 1Js (1D) Disomic Substitution Line With Resistance to Stripe Rust and Powdery Mildew - Wang, Yanzhen; Cao, Qiang; Zhang, Junjie; Wang, Siwen; Chen, Chunhuan; Wang, Changyou; Zhang, Hong; Wang, Yajuan; Ji, Wanquan (Frontiers in Plant Science, 2020)
Thinopyrum ponticum (2n=10x=70), a member of the tertiary gene pool of wheat (Triticum aestivum L.), harbors many biotic and abiotic stress genes. CH10A5, a novel disomic substitution line from a cross of T. aestivum cv. 7182 and Th. ponticum, was characterized by cytogenetics and molecular marker analysis. Cytological observations showed that CH10A5 contained 42 chromosomes and formed 21 bivalents at meiotic metaphase I. Genome in situ hybridization (GISH) analysis indicated that two of its chromosomes came from the J s genome of Th. ponticum, and wheat 15K array mapping and fluorescence in situ hybridization (FISH) revealed that chromosome 1D was absent from CH10A5. Polymorphic analysis of molecular markers indicated that the pair of alien chromosomes belonged to homoeologous group one, designated as 1J s . Thus, CH10A5 was a wheat-Th. ponticum 1J s (1D) disomic substitution line. Field disease resistance trials demonstrated that the introduced Th. ponticum chromosome 1J s was responsible for the resistance to both stripe rust and powdery mildew at the adult stage. Based on specific locus amplified fragment sequencing (SLAF-seq), 507 STS molecular markers were developed to distinguish exogenous genetic material from wheat. Of these, 49 STS markers could be used to specifically identify the genetic material of Th. ponticum. CH10A5 will increase the resistance gene diversity of wheat breeding materials, and the markers developed here will permit further tracing of heterosomal chromosome fragments in the future.